An examination of the coach-created talent development motivational climate in Canoe Slalom in the United Kingdom - Macdonald, S.; Allen, J. (International Sport Coaching Journal, 2019)
The purpose of this study was to examine the coach-created talent development motivational climate in Canoe Slalom in the United Kingdom using achievement goal theory, self-determination theory and transformational leadership. The participants were six (five male, one female) full-time Canoe Slalom talent development coaches and 24 athletes (13 male, 11 female). A multidimensional, mixed methods approach examined participants` perceptions of the motivational climate, transformational leadership behaviours, coaching practices, and coaching philosophies. Data were collected through questionnaires, interviews, and systematic observation. A summary of the coaching climate, practices, and philosophy was developed for each coach based on the perspectives of the athletes, coach, and observer. These were then compared and commonalities and differences amongst the coach-created climates were identified. The coaches created a motivationally adaptive (structured, relatedness supportive, individually-focused, task-involved) talent development motivational climate. However, the coaches varied in the extent to which the climate was autonomy supportive and intellectually stimulating. Analysis of the coaching climates using a learning continuums framework revealed two distinct forms of climate: behaviourist/structure and humanistic/agency. The implications for talent development and key stakeholders are discussed.